A new design method for PI–PD control of unstable processes with dead time. (January 2019) - Onat, Cem
Abstract: PID controllers are still widely practiced in the industrial systems. In the literature, many publications can be found considering PID controller design for unstable processes. However, owing to the structural limitations of PID controllers, generally, good closed loop performance cannot be achieved with a PID for controlling unstable processes and usually a step response with a high overshoot and oscillation is obtained. On the other hand, PI–PD controllers are proved to give very satisfactory closed loop performances for unstable processes. The paper presents a simple design method to tune parameters of a PI–PD controller for the control of the unstable processes with time delay. The proposed method is based on plotting the stability boundary locus, which is a locus dependent on the parameters of the controller and frequency, in the parameter plane. The method uses a new concept named centroid of the convex stability region. Simulation examples and an experimental application are given to illustrate the superiority of the proposed method over some existing ones. Highlights: The paper represents a novel method for PI–PD control of the unstable systems. The proposed method uses a new concept named centroid of convex stability region. Ability of being extended to uncertain plants of the proposed method by means of Kharitonov theorem is an important advantage.